Effective Methods in Teaching Vocabulary - Kholxodjaeva Dilfuza Shoakramovna (International Journal on Orange Technologies, 2021)
This article analyses the vocabulary of a language and vocabulary teaching methods and techniques and studies some methods, such as, Using demonstrations and showing pictures, teaching words in the context, reading the word and etc. It discusses that vocabulary is needed for expressing meaning and in using the receptive (listening and reading) and the productive (speaking and writing) skills. Article also studies that setting a good context is an essential prerequisite for vocabulary teaching as it helps in both engaging the attention of the lea